Gmina a Ochotnicze Straże Pożarne w wykonywaniu zadań w zakresie ochrony przeciwpożarowej - Kocowski, Tadeusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
One of the public tasks of the municipality are matters of public order and security of citizens and fire protection. In the area of the municipality they were made by volunteer fire brigades assisted in cash by the municipality. Changes in such asystem were caused by the emergence of anational rescue and firefighting system, hence the need to investigate the current model of these relations.
Keywords: Ochotnicze Straże Pożarne; ochrona przeciwpożarowa